Seventh international open encounter on video. - Joan Miró Foundation, Barcelona; Center of art and communication, Buenos Aires (Barcelona : Joan Miró foundation, 1977)
Action Spzace ; Aguilar, José Roberto ; Aknai, Thomas ; Almeida, Helena ; Altmann, Roberto ; Ambrosini, Claudio ; Anderson, David ; Anselmi, Anselmo ; Arlandi, Gian Franco ; Baladi, Roland ; Baldessari, John ; Bernstein, Judith ; Berteig, Garry C. ; Biggs, Robert ; Boero, Renata ; Boggeri, Vito ; Bonet, Eugeni ; Boyle, B.J. ; Bonora, Lola ; Brand, Heinz ; Burgy, Donald ; Byerley, Gerald ; etc.
Seventh international open encounter on video, Joan Miró foundation, Barcelona and Center of art and communication, Buenos Aires, february 1977
boek